Responsiveness of primary care services: development of a patient-report measure – qualitative study and initial quantitative pilot testing - Carolyn Tarrant; Emma Angell; Richard Baker; Mary Boulton; George Freeman; Patricia Wilkie; Peter Jackson; Fatimah Wobi; Diane Ketley (Health Services and Delivery Research, 2014)
Background: Primary care service providers do not always respond to the needs of diverse groups of patients, and so certain patients groups are disadvantaged. General practitioner (GP) practices are increasingly encouraged to be more responsive to patients’ needs in order to address inequalities. Objectives: (1) Explore the meaning of responsiveness in primary care. (2) Develop a patient-report questionnaire for use as a measure of patient experience of responsiveness by a range of primary care organisations (PCOs). (3) Investigate methods of population mapping available to GP practices. Design setting: PCOs, including GP practices, walk-in centres and community pharmacies. Participants: Patients and staff from 12 PCOs in the East Midlands in the development stage, and 15 PCOs across three different regions of England in stage 3. Interventions: To investigate what responsiveness means, we conducted a literature review and interviews with patients and staff in 12 PCOs. We developed, tested and piloted the use of a questionnaire. We explored approaches for GP practices to understand the diversity of their populations. Main outcome measures: (1) Definition of primary care responsiveness. (2) Three patient-report questionnaires to provide an assessment of patient experience of GP, pharmacy and walk-in centre responsiveness. (3) Insight into challenges in collecting diversity data in primary care. Results: The literature covers three overlapping themes of service quality, inequalities and patient involvement. We suggest that responsiveness is achieved through alignment between service delivery and patient needs, involving strategies to improve responsive service delivery, and efforts to manage patient expectations. We identified three components of responsive service delivery: proactive population orientation, reactive population orientation and individual patient orientation. PCOs tend to utilise reactive strategies rather than proactive approaches. Questionnaire development involved efforts to include patients who are ‘seldom heard’. The questionnaire was checked for validity and consistency and is available in three versions (GP, pharmacy, and walk-in centre), and in Easy Read format. We found the questionnaires to be acceptable to patients, and to have content validity. We produced some preliminary evidence of reliability and construct validity. Measuring and improving responsiveness requires PCOs to understand the characteristics of their patient population, but we identified significant barriers and challenges to this. Conclusions: Responsiveness is a complex concept. It involves alignment between service delivery and the needs of diverse patient groups. Reactive and proactive strategies at individual and population level are required, but PCOs mainly rely on reactive approaches. Being responsive means giving good care equally to all, and some groups may require extra support. What this extra support is will differ in different patient populations, and so knowledge of the practice population is essential. Practices need to be motivated to collect and use diversity data. Future work needed includes further evaluation of the patient-report questionnaires, including Easy Read versions, to provide further evidence of their quality and acceptability; research into how to facilitative the use of patient experience data in primary care; and implementation of strategies to improve responsiveness, and evaluation of effectiveness. Funding: The National Institute for Health Research Service Delivery and Organisation programme.